2011
DOI: 10.1246/cl.2011.1405
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Phenol from Benzene over Platinum-loaded Tungsten(VI) Oxide Photocatalysts with Water and Molecular Oxygen

Abstract: Tungsten(VI) oxide loaded with nanoparticulate platinum (Pt/WO3) was demonstrated for the first time to exhibit photocatalytic activity for direct synthesis of phenol from benzene using water and molecular oxygen as reactants under ultraviolet or visible light irradiation; the selectivity for phenol (e.g., 74% at 69% of benzene conversion) on Pt/WO3 photocatalysts was much higher than those on platinum-loaded titanium(IV) oxide (Pt/TiO2) photocatalysts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 21 publications
(15 reference statements)
0
34
0
Order By: Relevance
“…Abe et al reported the oxidation of benzene to phenol by using Pt loaded onto WO 3 , as a visible light photocatalyst. 151 The authors observed that the system composed by Pt/WO 3 showed higher selectivity for the phenol production (74% of selectivity) when compared with platinized or bare TiO 2 . It was hypothesized that the high selectivity is due to the presence of the platinum co-catalyst, which favors the twoelectron reduction of O 2 .…”
Section: View Article Onlinementioning
confidence: 99%
“…Abe et al reported the oxidation of benzene to phenol by using Pt loaded onto WO 3 , as a visible light photocatalyst. 151 The authors observed that the system composed by Pt/WO 3 showed higher selectivity for the phenol production (74% of selectivity) when compared with platinized or bare TiO 2 . It was hypothesized that the high selectivity is due to the presence of the platinum co-catalyst, which favors the twoelectron reduction of O 2 .…”
Section: View Article Onlinementioning
confidence: 99%
“…The rate of this reduction is regarded as much higher than that of the two-electron oxygen reduction (Eq. (4)) or H 2 O 2 consumption reaction [42], leading to higher activity of the NaOH-loaded WO 3 . To elucidate this proposed mechanism, we will plan to systematically investigate the formation of ·O 2 − or ·OOH radical by ESR or other technique.…”
Section: Photocatalytic Activitymentioning
confidence: 99%
“…However, since the main part in the wavelength distribution of sunlight and interior illuminations are visible light, photocatalysts that can utilize visible light has been desired for more efficient use. Tungsten oxide (WO 3 ) has been reported as such photocatalyst that can utilize visible light [3][4][5].…”
Section: Introductionmentioning
confidence: 99%